Abordagem Sociolinguística sobre o Ensino da Concordância de Número no Sintagma Verbal - Pedreira, Carlos Wilson de Jesus (2017)
n this research, we investigated the factors that concern to the verbal agreement of 3rd person plural in textual productions of students from 9th grade and the 3rd year of Secondary Education in two schools in the city of Juazeiro-BA, one public, located in a neighborhood, peripheral, and the other private, located next to the city center. The analysis was performed according to the Sociolinguistic Principles of Labov (LABOV, 1996, 1972). To do so, it analyzes the textual production of 78 pupils, on basis of two Textual Genres, being that 31 texts (13 Personal Reports and 18 Dissertative-Argumentative text) showed absence of verbal agreement. The 47 remaining texts (between personal account and Dissertative- Argumentative text) showed no occurrences of absence of verbal agreement. In general, the results showed us that, regardless of the level of schooling, or even to be a school whether public or private, the rate of non-verb agreement was still similar, as soon as in 08 productions of 9 year from public schools and 08 productions of the private school, totaling 16 productions and 08 productions of the 3rd grade of public school and 07 productions of the area, totaling 15 productions, presented deviations from the use of verbal agreement. We realized that the textual genre Personal Report was not so favorable to incidence of deviations of agreement, but the opinion texts, which is a kind of argumentation, the incidence of deviations of concordance was quite evident. However, it is perceived that many of these detours occur in structures verb-subject and with verbs that have less salience phonics as demonstrated by studies of Naro & Scherre (1997; 1999), Rodrigues (1987), Bortoni-Ricardo (1985).Thus, based on these data, we've developed and applied a sequence of activities on the verb-subject agreement, supported on the sociolinguistic principles, for which these students could better understand the relationship of agreement and, therefore, use them in more proficient way. Fact that has proved by comparison of the writings and the rewrites ones of thepupils, as well as by the reflection undertaken by the students during the exercises proposed in the didactic sequences.